Market influencers for ICT advancement in small states – a comparative analysis. Issue 3 (3rd July 2018) - Larios-Hernández, Guillermo Jesús; Reyes-Mercado, Pável
ABSTRACT: This paper analyzes the relationship between Information and Communications Technology (ICT) market drivers and the level of ICT usage in small states. Main arguments in the literature review refer to institutional, socioeconomic, and demographic factors to explain ICT usage. Through a multi-method approach, this paper takes a dataset of small states to explore the relationship between ICT market variables and Internet usage. Findings highlight the importance of underlying digital platforms. A typology of small states is provided for ICT market influencers and usage, showing a varying degree of heterogeneity. Given that the sample size available to study small states limits the use of traditional analytical techniques, this paper utilizes Qualitative Comparative Analysis and demonstrates that high usage levels of digital applications for businesses, consumers, and social-media are conditions that are sufficient, but not necessary, for ICT advancement to occur. Implications for theory development and policy making are discussed in terms of market incentives.